Analysis of the Alignment of Indonesian Language Textbook Content with the Content Standards of the Independent Learning Curriculum - Lagrima wijaya, Aicha; Harjono, Hary Soedarto; Rustam, Rustam (EDUTEC : Journal of Education And Technology, 2024)
This study aims to determine the alignment of the Indonesian language textbook content for Grade X (Phase E), used by SMK Baiturrahim Jambi students, with the learning outcomes (LO) specified in the Content Standards by the Assessment and Curriculum Standards Agency, Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia, within the "Merdeka Curriculum" framework. The learning outcomes cover four language skill elements: listening, reading and viewing, speaking and presentation, and writing. This research employs a descriptive analysis method, using the Indonesian language textbook Pembelajaran Unggul Bahasa Indonesia SMK/MAK Kelas X, published by PT Bumi Aksara in 2022, as the data source. Data were extracted from each chapter, focusing on the representation of language skills in the learning content and activities, and analyzed using qualitative descriptive techniques. The findings indicate that the listening skills content is highly aligned with the Content Standards, while the speaking skills content is poorly aligned, with a score of 17%. The reading skills content is also highly aligned, and the writing skills content shows a high level of alignment with the learning outcomes of the Indonesian language in the "Merdeka Curriculum."